A Study of the Effect of Additional Magnesium (Mg) on Erosion-Corrosion Resistance and Bending Strength in Aluminum A383 Alloy - Amiruddin, Arya Ahmad; Arma, Lukmanul Hakim; Arsyad, Hairul (EPI International Journal of Engineering, 2023)
In this study, evaluating the erosion-corrosion resistance and mechanical properties, especially the bending strength of aluminum alloy A383 with the addition of 4%, 6%, and 9% magnesium was investigated with variations in velocity (45l/h, 60l/h, and 75l/h). and angle variations (30º, 40º, and 50º) using 12% sodium hypochlorite solution. The test equipment used is an injection diaphragm pump in the recirculation system for 4 hours per sample. The results showed that the erosion-corrosion resistance of A383 alloy is proportional with the increase of magnesium addition to the alloy maximum weight loss occurs at an impact angle of 30° with a velocity of 75 l/h. The degradation decreased slightly with increasing the impact angle and decreasing velocity. Analysis of the erosion-corrosion mechanism shows that the corrosion process dominates material damage rather than erosion. The results of the bending test showed that the highest strength was A383 9% Mg which was 366.09 MPa, and the lowest bending strength was A383 material without magnesium addition which was 261.80 MPa. From these results, it can be concluded that the addition of magnesium (Mg) to aluminum alloy A383 contributes to increased corrosion resistance and increased bending strength.